DAMPAK MIGRASI E-FAKTUR KE CORETAX PADA PT ABC - Widyastuti, Andini; Yuhertiana, Indrawati (Program Studi Akuntansi Universitas Flores, 2026)
This study aims to describe the impact of the migration from the e-Faktur system to CoreTax on the efficiency of tax reporting at PT ABC. The background of this research arises from the efforts of the Directorate General of Taxes (DJP) in reforming tax administration through the implementation of CoreTax as an integrated digital system. The method used is qualitative with a descriptive approach, where data were collected through interviews, observations, and documentation involving two informants. The results show that CoreTax is able to improve tax reporting efficiency through data integration, reduction of input errors, and acceleration of the reporting process. Nevertheless, challenges such as system instability and limited internal technical support remain obstacles in its implementation. A SWOT analysis reveals that this system has great potential to support tax compliance but also faces the threat of user resistance if technical issues are not promptly resolved. This study recommends strengthening infrastructure and enhancing user training to fully optimize the benefits of CoreTax.